Long-term Outcomes of ABO-incompatible Pediatric Living Donor Liver Transplantation. Issue 10 (October 2018) - Honda, Masaki; Sugawara, Yasuhiko; Kadohisa, Masashi; Shimata, Keita; Sakisaka, Masataka; Yoshii, Daiki; Uto, Keiichi; Hayashida, Shintaro; Ohya, Yuki; Yamamoto, Hidekazu; Yamamoto, Hirotoshi; Inomata, Yukihiro; et al.
Abstract : Background: ABO-incompatible (ABOi) living donor liver transplantation (LDLT) has been performed to compensate for donor shortage. To date, few studies have reported detailed B-cell desensitization protocols and long-term outcomes of ABOi pediatric LDLT. Methods: Twenty-nine pediatric ABOi LDLT recipients were retrospectively analyzed. We compared the clinical outcomes between ABOi (n = 29) and non-ABOi (n = 131) pediatric LDLT recipients. Furthermore, we evaluated the safety and efficacy of our rituximab-based regimen for ABOi pediatric LDLT (2 ⩽ age < 18; n = 10). Results: There were no significant differences in the incidence of infection, vascular complications, biliary complications, and acute cellular rejection between ABOi and non-ABOi groups. The cumulative graft survival rate at 1, 3, and 5 years for non-ABOi group were 92.1%, 87.0%, and 86.1%, and those for ABOi group were 82.8%, 82.8%, and 78.2%, respectively. Rituximab-based desensitization protocol could be performed safely, and reduced CD19+ lymphocyte counts effectively. Although rituximab-treated ABOi group showed comparable clinical outcomes and graft survival rate, 2 patients developed antibody-mediated rejection. Conclusions: ABOi LDLT is a feasible option for pediatric end-stage liver disease patients. However, it should be noted that current desensitization protocol does not completely prevent the onset of antibody-mediated rejection in several cases. Abstract : The authors of this single-center retrospective study demonstrate that ABO incompatible (ABOi) LDLT is a feasible option for pediatric end-stage liver disease patients by comparing the clinical outcomes between ABOi and non-ABOi pediatric LDLT recipients as well as assessing the safety and efficacy of a rituximab-based desensitization protocol. Supplemental digital content is available in the text.